Means and methods of technical and tactical training fencers at the stage of specialized base training - Бакум, А. В. (Slobozhanskyi Herald of Science and Sport, 2011)
The theoretical analysis of modern means and methods used to improve technical and tactical skill of fencers the stage of specialized base training. Defining the core methods and tools used in technical and tactical training of fencers, as well as examined the use of computer modeling techniques in the preparation of fencing at the present stage.